(untitled) (Castilla. Estudios de Literatura, 2012)
Despite their strict contemporaneity, their probable common historic sources and plot similarities, John Dryden’s The Indian Emperour (1667) and Fernando de Zárate’s La Conquista de México (1668) theatrical plays convey two divergent visions of the American indigenous universe. In accordance with the theory of textual semantics, this work proposes to construct the pertinent evaluations related to the indigenous actors in these pieces and establish the narrative truth of some problematic enunciates, in order to suggest an alternative reading of Zárate’s work in relation to the teatro indiano.